Infographic Trends in Digital Media Communication from a Visual Communication Perspective - Syaputri, Intan Kurnia; Frenika, Maisya; Verolyna, Dita; Thadi, Robeet (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2025)
This study attempts to explore visual content on the Instagram account @pinterpolitik, which uses infographics as the main display. This researcher uses a qualitative-descriptive approach that analyzes the visual communication elements in the infographic display of the Instagram account @pinterpolitik. The criteria for selecting infographic content are based on the highest number of likes between March - April 2024. This study concludes that the @pinterpolitik account uses typography, illustration, and color play techniques in every infographic design displayed. Verbal and visual signs are intertwined to form an infographic display that is visually attractive and data-accurate.